Nicotine and novel tobacco products drive adverse cardiac remodeling and dysfunction in preclinical studies - Fried, Nicholas D.; Oakes, Joshua M.; Whitehead, Anna K.; Lazartigues, Eric; Yue, Xinping; Gardner, Jason D. (Frontiers in Cardiovascular Medicine, 2022)
Background: The heart undergoes structural and functional changes in response to injury and hemodynamic stress known as cardiac remodeling. Cardiac remodeling often decompensates causing dysfunction and heart failure (HF). Cardiac remodeling and dysfunction are significantly associated with cigarette smoking. Although cigarette smoking has declined, the roles of nicotine and novel tobacco products (including electronic cigarettes and heat-not-burn tobacco) in cardiac remodeling are unclear. In this perspective, we present evidence demonstrating maladaptive cardiac remodeling in nicotine-exposed mice undergoing hemodynamic stress with angiotensin (Ang)-II infusion and review preclinical literature linking nicotine and novel tobacco products with cardiac remodeling and dysfunction. Methods: Adult, male C57BL/6J mice were exposed to room air or chronic, inhaled nicotine for 8 weeks. A subset of mice was infused with Ang-II via subcutaneous osmotic mini-pumps during the final 4 weeks of exposure. Left ventricular structure and function were assessed with echocardiography. Results: Chronic, inhaled nicotine abrogated Ang-II-induced thickening of the left ventricular posterior wall, leading to reduced relative wall thickness. Ang-II infusion was associated with increased left ventricular mass index in both air- and nicotine-exposed mice. Conclusions: These changes suggest a phenotypic shift from concentric hypertrophy to eccentric hypertrophy in nicotine-exposed, hemodynamically-stressed mice which could drive heart failure pathogenesis. These findings join a growing body of animal studies demonstrating cardiac remodeling and dysfunction following nicotine and electronic cigarette exposure. Further exploration is necessary; however, clinicians and researchers should not overlook these emerging products as potential risk factors in the pathogenesis of cardiac remodeling and associated diseases including HF.